Light-induced exposure of the cytoplasmic end of transmembrane helix seven in rhodopsin - Abdulaev, Najmoutin G. (The National Academy of Sciences, 1998)
A key step in signal transduction in the visual cell is the light-induced conformational change of rhodopsin that triggers the binding and activation of the guanine nucleotide-binding protein. Site-directed mAbs against bovine rhodopsin were produced and used to detect and characterize these conformational changes upon light activation. Among several antibodies that bound exclusively to the light-activated state, an antibody (IgG subclass) with the highest affinity (K(a) ≈ 6 × 10(−9) M) was further purified and characterized. The epitope of this antibody was mapped to the amino acid sequence 304–311. This epitope extends from the central region to the cytoplasmic end of the seventh transmembrane helix and incorporates a part of a highly conserved NPXXY motif, a critical region for signaling and agonist-induced internalization of several biogenic amine and peptide receptors. In the dark state, no binding of the antibody to rhodopsin was detected. Accessibility of the epitope to the antibody correlated with formation of the metarhodopsin II photointermediate and was reduced significantly at the metarhodopsin III intermediate. Further, incubation of the antigen–antibody complex with 11-cis-retinal failed to regenerate the native rhodopsin chromophore. These results suggest significant and reversible conformational changes in close proximity to the cytoplasmic end of the seventh transmembrane helix of rhodopsin that might be important for folding and signaling.